2010
DOI: 10.3109/17477160903473697
|View full text |Cite
|
Sign up to set email alerts
|

Self-esteem and quality of life in obese children and adolescents: A systematic review

Abstract: Although an increasing number of children and adolescents are becoming obese, the psychological morbidities associated with obesity are not well established. Existing reviews report modest associations between obesity and global self-esteem. However, none have examined how this affects multi-component assessments of self-esteem and quality of life in young people with defined obesity. A literature search identified 17 self-esteem and 25 quality of life studies of cross-sectional, longitudinal or intervention d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
381
2
32

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 466 publications
(461 citation statements)
references
References 63 publications
(308 reference statements)
26
381
2
32
Order By: Relevance
“…Childhood overweight is associated with serious consequences for health and well-being both during childhood years and in adulthood (3)(4)(5)(6)(7). Effective early preventive strategies are therefore urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Childhood overweight is associated with serious consequences for health and well-being both during childhood years and in adulthood (3)(4)(5)(6)(7). Effective early preventive strategies are therefore urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…High self-esteem has been associated with numerous positive outcomes, such as overall psychosocial adjustment (Griffiths, Parsons, & Hill, 2010). Researchers (e.g., Baumeister, 2011;Bois et al, 2000;Crocker & Luhtanen, 2003;Turner, 2010) have posited that individuals determine their self-esteem by comparing their attributes (e.g., physical appearance) to their self-standards (e.g., internalized societal appearance norms).…”
Section: Self-esteem and Dietary Restraintmentioning
confidence: 99%
“…A study carried out in 2005 found negative results in treatment for these children (2) , while another carried out in 2008 (7) , showed favorable treatment results, reducing harm for quality of life. Better knowledge on patients and family members' psychosocial demands may contribute to more effective health actions (8) .…”
Section: Introductionmentioning
confidence: 99%
“…Immediate morbidities (hepatic steatosis, sleep apnea, slipped capital femoral epiphysis and type 2 diabetes) can occur in overweight and obese children and adolescents (1) . Psychosocial repercussions, however, such as low self-esteem (2) , stigmatization and compromised quality of life, are the most significant in the short term (1) . The increase in the Body Mass Index (BMI) is inversely proportional to children and adolescents' quality of life (2)(3)(4)(5)(6)(7)(8) .…”
Section: Introductionmentioning
confidence: 99%